Novel Stilbene-Nitroxyl Hybrid Compounds Display Discrete Modulation of Amyloid Beta Toxicity and Structure - Hilt, Silvia; Liu, Ruiwu; Maezawa, Izumi; Rojalin, Tatu; Aung, Hnin H.; Budamagunta, Madhu; Slez, Ryan; Gong, Qizhi; Carney, Randy P.; Voss, John C. (Frontiers in Chemistry, 2022)
Several neurodegenerative diseases are driven by misfolded proteins that assemble into soluble aggregates. These “toxic oligomers” have associated with a plethora of cellular dysfunction and dysregulation, however the structural features underlying their toxicity are poorly understood. A major impediment to answering this question relates to the heterogenous nature of the oligomers, both in terms of structural disorder and oligomer size. This not only complicates elucidating the molecular etiology of these disorders, but the druggability of these targets as well. We have synthesized a class of bifunctional stilbenes to modulate both the conformational toxicity within amyloid beta oligomers (AβO) and the oxidative stress elicited by AβO. Using a neuronal culture model, we demonstrate this bifunctional approach has the potential to counter the molecular pathogenesis of Alzheimer’s disease in a powerful, synergistic manner. Examination of AβO structure by various biophysical tools shows that each stilbene candidate uniquely alters AβO conformation and toxicity, providing insight towards the future development of structural correctors for AβO. Correlations of AβO structural modulation and bioactivity displayed by each provides insights for future testing in vivo. The multi-target activity of these hybrid molecules represents a highly advantageous feature for disease modification in Alzheimer’s, which displays a complex, multifactorial etiology. Importantly, these novel small molecules intervene with intraneuronal AβO, a necessary feature to counter the cycle of dysregulation, oxidative stress and inflammation triggered during the earliest stages of disease progression.